2014
DOI: 10.1016/j.jana.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Nurse-Initiated and -Managed Antiretroviral Therapy (NIMART) in Practice, Education, Policy, and Regulation in East, Central, and Southern Africa

Abstract: In sub-Saharan Africa, nurses and midwives perform many HIV service delivery tasks, such as diagnosis of HIV and prescription of antiretroviral therapy (ART), which used to be the responsibility of physicians. While this task shifting is critical to scaling-up HIV services in Africa, the extent of HIV task shifting is not well understood. A survey of senior nursing leadership teams from 15 African countries was carried out to describe the extent of nurse-initiated and -managed antiretroviral therapy (NIMART) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 5 publications
1
53
0
Order By: Relevance
“…19 However, this needs to be expanded and implemented on a much larger scale. 20,21 The need to expand nurse training will increase with the planned implementation of HIV-1 DNA PCR testing of exposed neonates at birth. 22 As this is being newly implemented, healthcare workers in labour wards and nurseries may not be as experienced with DBS specimen collection as those in immunisation clinics.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, this needs to be expanded and implemented on a much larger scale. 20,21 The need to expand nurse training will increase with the planned implementation of HIV-1 DNA PCR testing of exposed neonates at birth. 22 As this is being newly implemented, healthcare workers in labour wards and nurseries may not be as experienced with DBS specimen collection as those in immunisation clinics.…”
Section: Discussionmentioning
confidence: 99%
“…23,7175 Ensuring that HIV services are integrated into a highly functional health system at the national, subnational, and facility levels has become even more imperative as the challenges of retaining women and children living with HIV in care over a lifetime have become more apparent with the scale-up of Option B+.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 survey of national nursing leaders that included representatives from 12 Global Plan countries found that nurses were prescribing and managing antiretroviral therapy for pregnant women in 9 of these 12 countries. 23 The example of Lesotho illustrates how nurse-initiated and nurse-managed antiretroviral therapy models for pregnant women have facilitated expansion of antiretroviral therapy services, including through integration with MNCH services (see Country Case Study 2). Ongoing support for the professional growth and development of the entire health care workforce will be important to maintain and expand quality HIV-related services for pregnant and breast-feeding women and their children.…”
Section: The Essential Role Of Task Sharingmentioning
confidence: 99%
“…1, 8 The delegation of responsibility for diagnosing and initiating treatment for HIV, referred to as “task shifting,” has moved to nurses in more countries, commensurate with their training. 9 However, in the face of an overall shortage of health professionals in Africa, task shifting is not an adequate solution in itself.…”
Section: Facing the Challengesmentioning
confidence: 99%